The Geomorphology of Submarine Channel Systems of the Northern Line Islands Ridge, Central Equatorial Pacific Ocean - Gardner, James V.; Peakall, Jeffrey; Armstrong, Andrew A.; Calder, Brian R. (Frontiers in Earth Science, 2020)
More than 844,000 km2 of the northern Line Islands Ridge mapped with multibeam bathymetry and backscatter provide unprecedented views of the geomorphology of this isolated area in the central equatorial Pacific Ocean. A compilation of all available multibeam data in the area reveals six extensive submarine dendritic channel systems that encompass a combined drainage area that exceeds 60,000 km2. The channel systems are incised into the surface of basins surrounded by small guyots and seamounts that make up a discontinuous rim around the summit of the northern Line Island Ridge. The channels have mostly straight or gently curved well-developed tributaries and main reaches. Although the Line Island Ridge has been dated at 86 to 68 Ma old, the channels occur on the surface and are not buried by any significant sediment accumulations. Levees are very rare along the channel banks and no submarine fans were found where the channels merge with the adjacent abyssal basins. There is sparse evidence of slope failures or landslides throughout the ridge. The presence of plunge pools below the northwest escarpment, together with the well-defined channel incisions, suggests the channels might be relatively recent (perhaps late Neogene or even younger) features developed long after the ridge subsided more than a kilometer below sea level.